ANALYSIS OF THE EFFECT OF LABOUR AND EDUCATION LEVELS ON ECONOMIC GROWTH IN NORTH LUWU REGENCY - Hartini Hartini; Muh Yusuf Qamaruddin; Muhammad Hadis Badewi (UNIVERSITAS PGRI MADIUN, 2025)
This study aims to determine: (1) The Effect of Labour on Economic Growth in North Luwu Regency. (2) The Effect of Education Level on Economic Growth in North Luwu Regency. (3) The effect of labour and education level together on economic growth in North Luwu Regency. This type of research is quantitative. The type of data is secondary data. This study uses time series data issued by the Central Bureau of Statistics (BPS) of North Luwu Regency at constant 2010 prices, the data collected for the last 8 years. The data analysis method used in this research is Multiple Linear Regression. The results of this study indicate that: (1) Labour has a negative and significant effect on Economic Growth in North Luwu Regency. (2) Education level has a positive and significant effect on economic growth in North Luwu Regency. (3) Labour force and education level together affect economic growth in North Luwu Regency.